Influence of Plyometric Resistance Exercises on Metabolic Syndrome Risk Factors in Obese College Students - MAHABOOBJAN, Dr.A.; K.P., Mr.HUSSAINSAB; SOWMIYA, Dr.V. (South Eastern European Journal of Public Health, 2024)
The purpose of the study was to find out the influence of plyometric resistance exercises on metabolic syndrome risk factors in obese female college students. To achieve the purpose of the study, thirty female students were selected from various departments of Bharathidasan University, Tiruchirappalli, Tamilnadu. The age of the subjects were ranged between 18 to 21 years. The subjects were randomly assigned in to two equal groups namely, plyometric resistance exercises training group (PRETG) (n=15) and control group (CG) (n=15). The dependent metabolic syndrome risk factors such as, Waist Circumference (cm), Blood Glucose (mg/dL), Triglyceride (TG, mg/dL), HDL-C (mg/dL), LDL-C (mg/dL) and Total Cholesterol (mg/dL) were selected for this study and the unit of measurement in cm, mg/dL, TG, mg/dL, mg/dL, mg/dL and mg/dL respectively. All the subjects were tested prior to and immediately after the experimental period on the selected dependent variable. The experimental groups underwent respective training period for five days per week for of twelve weeks. The control group was not given any sort of training except their routine. All subjects were tested on selected criterion variables. The collected data from the factors were statistically analysed with ‘f’ test to find out the significant improvement between pre and post test. In all cases the criterion for statistical significance was set at 0.05 level of confidence (P<0.05). The result of the study indicates that the difference exit on Waist Circumference, Blood Glucose, Triglyceride, HDL-C, LDL-C and Total Cholesterol of obese female college students due to the influence of 12 weeks of plyometric resistance exercises training.